SERPENTINIZATION HISTORY IN MANTLE SECTION FROM A FOSSIL SLOW-SPREADING RIDGE SEQUENCE: EVIDENCES FROM POMAIA QUARRY (SOUTHERN TUSCANY, ITALY) - Donatio, Deborah; Marroni, MIchele; Rocchi, Sergio (Ofioliti, 2013)
In the Pomaia quarry (Southern Tuscany, Italy) a mantle section consisting of peridotites belonging to the Internal Ligurian units is exposed. This mantle section, that is regarded as representative of the Jurassic oceanic lithosphere of the Ligure-Piemontese oceanic basin, provides the opportunity for a complete reconstruction of the serpentinization history of the peridotites by studying of the systems of serpentine-bearing veins. The tectono-magmatic history reconstructed for the peridotites includes the development of tectonitic textures followed by the intrusion of gabbro dykes and stocks. Subsequently, the gabbros as well as their boundaries with the peridotites are cut by high-T mylonitic shear zones, and then by thick cataclastic shear zones. The peridotites are cut by several systems of serpentine-bearing veins originated in the host rocks after the intrusion of gabbroic melts. All the structural, petrographic and mineralogical data, indicate that in the studied mantle a sequence of veins sequence developed. This sequence includes: 1) veins filled by lizardite with blocky texture 2) veins filled by chrysotile with both blocky and fibrous texture and 3) veins filled by antigorite. This paper provides for the first time the evidence that the serpentinization in the peridotites from the Internal Ligurian units is associated to a sequence of different events of veining. These events developed in response to a history dominated by alternance of tectonic-controlled and magmatic-controlled hydration of the peridotites in a slow-spreading ridge setting. According to this reconstruction, the Pomaia peridotites represents the core of a megamullion built-up dur- ing an oceanic extensional tectonic stage in in a slow-spreading ridge system.